Effects of integrin‐linked kinase on human corpus cavernosum smooth muscle cell cytoskeletal organisation. (22nd May 2012) - Hao, Y.‐C.; Yu, L.‐P.; Li, Q.; Zhang, X.‐W.; Zhao, Y.‐P.; He, P.‐Y.; Xu, T.; Wang, X.‐F.
Summary We investigated the effects of integrin‐linked kinase (ILK) on the in vitro attachment, spreading, migration and microfilament dynamics of human corpus cavernosum smooth muscle cells. ILK small interfering RNA (siRNA) was used to transfect human corpus cavernosum smooth muscle cells; and cell attachment, spreading and migration were assessed. Additionally, microfilament dynamics were evaluated using Alexa Fluor 488 and phalloidin staining. We found that ILK gene knock‐down significantly inhibited human corpus cavernosum smooth muscle cell attachment, spreading and migration. Moreover, blocking the expression of ILK disturbed actin cytoskeleton reorganisation and morphology in human corpus cavernosum smooth muscle cells. These results show that the targeting of ILK with siRNA significantly inhibited cell attachment, spreading, migration and microfilament dynamics in human corpus cavernosum smooth muscle cells. These findings indicate that ILK might be a potential therapeutic molecular target for the treatment of erectile dysfunction.